Ticagrelor or dipyridamole plus aspirin may be a promising antiplatelet therapy in patients with minor stroke or transient ischemic attack: a bayesian network meta-analysis - Qin, Shiran; Gao, Si; Xu, Dandan; Zhang, Li; Luo, Yanmei; Guo, Sitong (Frontiers in Pharmacology, 2025)
BackgroundThe efficacy and safety of different antiplatelet in minor strokes or transient ischemic attacks (TIAs) remains controversial.MethodsWe searched PubMed, Embase, Web of Science and the Cochrane Library to identify all eligible articles until 12 September 2024. Efficacy outcomes were all-cause mortality, excellent outcome, functional independence and recurrent stroke. Safety outcomes were any types of bleeding and intracerebral hemorrhage (ICH). The associations were calculated for the overall data by using the odds ratios (ORs).Results12 high-quality studies with 10 RCTs and 2 Non-RCTs were included, involving 61,281 patients with minor strokes or TIAs. Ticagrelor + Aspirin was significantly more effective than Clopidogrel + Aspirin in preventing post-stroke neurological dysfunctions (mRS 0–1), recurrent stroke and major vascular events for up to 90 days. But Ticagrelor + Aspirin is associated with an increased risk of any bleeding and mild bleeding at 90 days, and there is no significant difference in other bleeding risks. The risk of any bleeding in Dipyridamole + Aspirin is not significantly different from that in Aspirin, and is even significantly lower than in Ticagrelor. Compared with other dual antiplatelet therapies (DAPTs), Dipyridamole + Aspirin had no significant difference in the risk of all-cause mortality and major vascular events during follow-up.ConclusionFor minor strokes or TIAs with a low bleeding risk or CYP2C19 loss-of-function alleles, Ticagrelor + Aspirin may be a better choice than Clopidogrel + Aspirin. Due to limited studies, the superiority of Dipyridamole + Aspirin is still difficult to conclude, and further high-quality studies are needed to verify the benefits of Dipyridamole + Aspirin in minor stroke or TIAs.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024537462